2005
DOI: 10.1073/pnas.0506624102
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological modulation of pain-related brain activity during normal and central sensitization states in humans

Abstract: Abnormal processing of somatosensory inputs in the central nervous system (central sensitization) is the mechanism accounting for the enhanced pain sensitivity in the skin surrounding tissue injury (secondary hyperalgesia). Secondary hyperalgesia shares clinical characteristics with neurogenic hyperalgesia in patients with neuropathic pain. Abnormal brain responses to somatosensory stimuli have been found in patients with hyperalgesia as well as in normal subjects during experimental central sensitization. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
207
2
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(220 citation statements)
references
References 71 publications
9
207
2
2
Order By: Relevance
“…In anesthetized rats, gabapentin modulates the BOLD signal in several areas involved in nociceptive processing, for example, by increasing activity in thalamus and periaqueductal gray matter and decreasing it in amygdala (38). In humans, even a single dose of gabapentin can modulate brain responses to noxious mechanical stimuli (39). Moreover, half of our patients used tricyclic antidepressants (amitriptylin or nortriptylin), often administered in low doses to treat chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…In anesthetized rats, gabapentin modulates the BOLD signal in several areas involved in nociceptive processing, for example, by increasing activity in thalamus and periaqueductal gray matter and decreasing it in amygdala (38). In humans, even a single dose of gabapentin can modulate brain responses to noxious mechanical stimuli (39). Moreover, half of our patients used tricyclic antidepressants (amitriptylin or nortriptylin), often administered in low doses to treat chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological fMRI is an ideal noninvasive tool that can be used to determine the effects of drugs on brain activation. An fMRI study in humans by Iannetti et al [69] demonstrated the complex effects of the neuromodulating drug gabapentin on brain activation. The most pronounced effect was a reduction in stimulus-induced brain deactivation following central sensitization.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of low-frequency noise in the BOLD fMRI signal renders it poorly sensitive to changes occurring over periods longer than minutes (Zarahn et al, 1997); thus baseline functional "states" are difficult to reliably address with BOLD, though some studies have attempted to do so (Small et al, 2000, Rombouts et al, 2007 and biophysical models of resting BOLD contrast continue to be developed (He and Yablonskiy, 2007). BOLD fMRI time series data acquired at rest can also be used to assess functional connectivity (Biswal and Ulmer, 1999), default mode networks (Raichle et al, 2001, Greicius et al, 2003, Greicius et al, 2004, or functional state variation within prior regions of interest (ROIs) (Iannetti et al, 2005). …”
Section: Introductionmentioning
confidence: 99%